Sexual violence on campus : power-conscious approaches to awareness, prevention, and response - Linder, Chris (Great debates in higher education, 2024)
Rates of sexual violence on college campuses in the U.S. have not changed for more than 60 years. People who cause harm target women of color, queer and trans students, and disabled students at even higher rates than their peers. In Sexual Violence on Campus, Chris Linder examines oppression as the root of violence, with a specific focus on the intersections of racism, sexism, and sexual violence. Using a power-conscious framework, Linder examines well-intended practices related to awareness, prevention, and response of sexual violence on college campuses, highlighting some of the challenges with over-relying on one-size-fits-all strategies for addressing sexual violence. The first edition of this book received widespread praise for providing clear and accessible examples of problems with curren t practices, along with recommendations for improving practice. Those examples have been enhanced in the second edition of this text. Reframing the discussion from focusing on "perpetrators" to "people who cause harm," this updated edition includes a new chapter examining the relationship between harm and oppression, challenging practitioners and scholars to consider new ways of thinking about sexual harm and people who cause harm. By focusing on why people engage in harmful sexual behavior, we may improve our ability to prevent harm from happening in the first place.